Health crisis and quarantine measures in Peru: Effects on livelihoods of coffee and potato farmers - Vargas, R.; Fonseca, C.; Hareau, Guy; Ordinola, M.; Pradel, W.; Robiglio, V.; Suarez, V. (Elsevier, 2021)
This study contrasts the short-term effects of the quarantine measures implemented to contain the COVID-19 disease on the production and commercialization strategies of potato and coffee producers in Peru. Potato farmers appeared more impacted by the shock due to disruptions in the commercialization channels, leading to lower sales volumes and prices. In the near future, both potato and coffee farmers risk severe capital losses that are likely to affect the next agricultural season. Changes in household consumption patterns and intentions to introduce new crops to improve food security were reported, along with some concerns about long-term effects on the health and nutritional status of the households.